Suicidal behaviour - Walton, Hendrik Johannes (Department of Psychiatry and Mental Health, 2020)
Man is not always plainly discernible in scientific writings about him. His individuality denied, in many psychological studies man becomes a cipher. Science demands useful generalisations, and psychiatry is in part so unsatisfactory in discipline precisely because human life is complex. To affect an impression of simplicity when encountering bewildering diversity, although usual remains foolish, particularly when important matters are being dealt with. Suicidal behaviour is important, because it is common and touches the lives of many people. When hundreds of people presented themselves after behaving self-destructively, it seemed gradually to emerge that suicidal persons do resemble each other, and that there are aspects of similarity in their personalities and their suicidal acts. Psychological study of people is a worthy occupation now that we have lately learning how al men pass the major portion of their emotional lives in secret, their continuing passions hidden not only from their close associates but, indeed from themselves.